Design of electronically tunable first order allpass filter using OTAs with gain controllability - Prommas, Thawach; Jaikla, Winai; Suwanjan, Peerawut; Silapan, Phamorn (My University, 2013)
This paper presents current-mode first-order allpass filter using three operational transconductance amplifiers (OTAs) and grounded capacitor. The use of grounded capacitor makes the circuit more suitable for integrated circuit implementation. The current gain and phase shift can be independently controlled with electronic method. The circuit has high output impedance which enables easy cascading in the current mode circuits. The PSpice simulation results are depicted. The given results agree well with the theoretical anticipation. © 2013 IEEE.
Keywords: all-pass filter; Current-mode; first-order filter; integrated circuit; OTA